1993
DOI: 10.1080/09064719309410226
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Nitrous Oxide from Animal Manure in Dungheaps

Abstract: Concentrations of N 2 0 in gas samples taken from dungheaps of cattle and pig manure were up to 100 times greater than the atmospheric concentration. The concentrations varied little with time but tended to increase with depth. The concentrations were less in fresh manure than in stored manure, and less in cattle manure than in pig manure. The rate of release of N 2 0 from the manure surface was also determined. The mean rate from stored pig manure was 1 1 mg N20-N m-' h-', which is low compared to typical tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 9 publications
0
10
0
3
Order By: Relevance
“…The di!erence in emission pattern may re#ect that the temperature in these two experiments was high in a longer period than in the present study. The emission was low compared with emissions from untreated manure heaps determined by Sibbesen and Lind (1993) and Petersen et al (1998).…”
Section: Gaseous Emissionsmentioning
confidence: 58%
See 1 more Smart Citation
“…The di!erence in emission pattern may re#ect that the temperature in these two experiments was high in a longer period than in the present study. The emission was low compared with emissions from untreated manure heaps determined by Sibbesen and Lind (1993) and Petersen et al (1998).…”
Section: Gaseous Emissionsmentioning
confidence: 58%
“…. , air temperature Sibbesen and Lind (1993). The open structure of the deep litter has facilitated a high convection of air through the organic material, which has diluted the gases and reduced N O and CH formation, or induced CH oxidation.…”
Section: ¹Emperature and Gas Concentration In The Compostmentioning
confidence: 99%
“…Mahimairaja et al (1995) did not detect N 2 O production from fresh manures of poultry, horse, swine, dairy cattle or sheep. Sibbesen and Lind (1993) found that concentrations of N 2 O at any depth in solid manure piles were higher in sow and piglet manure than in dairy cattle manure. Furthermore, the concentration of N 2 O was higher in 1-mo old piles compared with fresh manure piles.…”
mentioning
confidence: 89%
“…The N 2 O emitted from untreated manure on pastures is a byproduct of nitrification and denitrification [19]. The annual emissions of this GHG are estimated as (Eq.…”
Section: A Baseline Scenariosmentioning
confidence: 99%